P959 Handheld echocardiography in a real world scenario: concordances compared to standard echo reports. (17th January 2020) - David Lechinewski, L; Vieira, I P; Clausell, N; Moura, L A Z; Barnes, M; Tsang, T; Gavazzoni Blume, G
Abstract: Background: Handheld echocardiography devices(HH) arise as a common tool in clinical examination and screening for various cardiovascular disorders. Despite of it, studies with this method are small, with unselected patients and limited scope of diagnostic comparison. Purpose: Assess the usefulness of the new miniaturized HH and compare its concordances with the standard high definition echocardiography study(STD). Methods: Between April and May of 2016 adult patients who were scheduled to regular STD, were also submitted to a HH exam. Experienced sonographers performed and an experienced echocardiographer reviewed the STD exam, and an experienced echocardiographer performed and reviewed the HH study - reviewers were blinded to the other study results. STD exams included 2-dimensional images, Color Doppler and hemodynamics analysis. With the HH hemodynamic assessment was not performed as the machine does not include such technology. Agreement between the reports was analyzed. Results: 110 patients were included. Mean age was 62.4 ± 16.7 years. The κ values(Table) show good correlation between HH and STD on the analysis of left ventricular global and segment functions, right ventricle size and function, mitral and aortic stenosis. On the evaluation of left ventricle hypertrophy, mitral and aortic regurgitations the correlation was modest, while poor correlation was found for pulmonary and tricuspid regurgitations. Conclusion: In a daily practice scenario with experienced hands, HH demonstrates good results for the assessment of ventricles size and function, while the evaluation of right heart valves was the least reliable performance. Dissemination of HH should occur with considerations and caution.